How do you find the zeroes of f (x) =10x^5 + 2x^4 − 75x^3 − 15x^2 + 125x + 25f(x)=10x5+2x4−75x3−15x2+125x+25?
1 Answer
Factor by grouping twice, then use the difference of squares identity twice and hence find zeros:
+-sqrt(10)/2±√102 ,+-sqrt(5)±√5 ,-1/5−15
Explanation:
The difference of squares identity can be written:
a^2-b^2 = (a-b)(a+b)a2−b2=(a−b)(a+b)
Factor by grouping:
f(x) = 10x^5+2x^4-75x^3-15x^2+125x+25f(x)=10x5+2x4−75x3−15x2+125x+25
= (10x^5+2x^4)-(75x^3+15x^2)+(125x+25)=(10x5+2x4)−(75x3+15x2)+(125x+25)
= 2x^4(5x+1)-15x^2(5x+1)+25(5x+1)=2x4(5x+1)−15x2(5x+1)+25(5x+1)
= (2x^4-15x^2+25)(5x+1)=(2x4−15x2+25)(5x+1)
= (2x^4-10x^2-5x^2+25)(5x+1)=(2x4−10x2−5x2+25)(5x+1)
= ((2x^4-10x^2)-(5x^2-25))(5x+1)=((2x4−10x2)−(5x2−25))(5x+1)
= (2x^2(x^2-5)-5(x^2-5))(5x+1)=(2x2(x2−5)−5(x2−5))(5x+1)
= (2x^2-5)(x^2-5)(5x+1)=(2x2−5)(x2−5)(5x+1)
= ((sqrt(2)x)^2-(sqrt(5))^2)(x^2-(sqrt(5))^2)(5x+1)=((√2x)2−(√5)2)(x2−(√5)2)(5x+1)
= (sqrt(2)x-sqrt(5))(sqrt(2)x+sqrt(5))(x-sqrt(5))(x+sqrt(5))(5x+1)=(√2x−√5)(√2x+√5)(x−√5)(x+√5)(5x+1)
Hence
+-sqrt(5)/sqrt(2) = +-sqrt(10)/2±√5√2=±√102
+-sqrt(5)±√5
-1/5−15